Pengaruh Manajemen Sumber Daya Manusia Tridharma Perguruan Tinggi Terhadap Peningkatan Mutu Dosen PTS - Arif Hidayat; Emanuel M. Bayudhirgantara (Journal on Education, 2023)
implementation of Tri Dharma Human Resource Management in Higher Education, a lecturer has three main tasks, namely: (1) education and teaching; (2) research; and (3) community service. The general objective of this research is to find out and analyze the influence of Tri Dharma Higher Education HRM on Improving the Quality of PTS Lecturers. Interpretation and analysis of research results, the following general conclusions are obtained: (1). There is the influence of MSDM in the Education and Teaching Sector on improving the quality of lecturers at STIE IGI; (2). There is the influence of MSDM Research on improving the quality of lecturers at STIE IGI; (3). There is the influence of MSDM in the Community Service Sector on improving the quality of lecturers at STIE IGI; (4). There is the influence of the MSDM for Education and Teaching, the MSDM for Research and the MSDM for Community Service together to improve the quality of lecturers at STIE IGI; (5). There is the influence of MSDM in the Education and Teaching Sector on improving the quality of lecturers at STIE Wibawa Karta Raharja; (6). There is the influence of MSDM Research on improving the quality of lecturers at STIE Wibawa Karta Raharja; (7). There is the influence of MSDM in the Community Service Sector on improving the quality of lecturers at STIE Wibawa Karta Raharja; (8). There is influence from the MSDM for Education and Teaching, the MSDM for Research and the MSDM for Community Service together to improve the quality of lecturers at STIE Wibawa Karta Raharja; (9). There is an influence of MSDM in the Education and Teaching Sector on improving the quality of lecturers at STMIK MIC (10). There is the influence of MSDM Research on improving the quality of lecturers at STMIK MIC; (11). There is the influence of MSDM in the Community Service Sector on improving the quality of lecturers at STMIK MIC; (12). There is the influence of the MSDM for Education and Teaching, the MSDM for Research and the MSDM for Community Service together to improve the quality of lecturers at STMIK MIC; (13) There are supporting and inhibiting factors for the quality of lecturers at STIE IGI, STIE Wibawa Karta Raharja, STMIK MIC through the implementation of Tri Dharma Higher Education HRM. The research findings are that of the three components of the Tri Dharma of Higher Education, research and publication are things that are difficult for lecturers to do, while there are demands to publish the results of their research in reputable international journals which have a significant effect on improving the quality of lecturers.